Rethinking Peru and its peasantry: Comment to "The peasant rounds and the defeat of the Shining Path" - Brachet-Márquez, Viviane (1996)
This book represents a unique achievement of Latin American social anthropology that goes beyond, however, the limits of this discipline. In a volume that, despite being a compilation, constitutes a highly integrated whole and brings together virtues that are rarely found together in a single work: rigorous theoretical seriousness, high-quality field observation (despite extremely difficult and dangerous conditions) and literary excellence. This book is required reading for the contemporary Peru specialist as well as for the general reader interested in understanding the reason for the outcome of one of the bloodiest guerrillas in Latin America.